UPAYA PELESTARIAN EKOSISTEM HUTAN AIR PAYAU DALAM MENJAGA KELESTRAIAN TATANAN EKOLOGIS (JURNAL SPASIAL, 2014)
Changes in forest ecosystems of brackish water in Indonesia has reached the alarming level. Center for the Study of Marine Fisheries and Bung Hatta University in 2005 mentioned, brackish water forest area in West Sumatra reached 39 832 hectares. Mentawai district has an area of 32,600 hectares of mangrove forests, West Pasaman area of 6273.5 hectares. Results showed that the level of damage is highest in the district of Padang Pariaman, 80 percent or comparable 160 hectares. As in West Pasaman reached 30% and the Mentawai Islands as much as 20%. For the city of Padang, the forest area of brackish water no more than 10 hectares. The forest is only found in the Banana River. Others mostly already built housing or for tourism.